Testing of Sodium Saccharin Levels in Hard Candy with High Performance Liquid Chromatography (HPLC) Method: Pengujian Kadar Natrium Sakarin Pada Permen Keras dengan metode Kromatografi Cair Kinerja Tinggi (KCKT) - Putri, Nezly Nurlia; Ghifari, Muhammad Syafa Al; Pujowati, Siti Nurlaeni (Universitas Muhammadiyah Sidoarjo, 2024)
Hard candy is a processed food resulting from the boiling of a mixture of sugar with food additives (BTP). The use of BTP is restricted in processed food. One type is sodium saccharin. The purpose of this study was to determine the level of sodium saccharin in hard candy with High Performance Liquid Chromatography (HPLC) instrument. The test procedure consists of making a solution of standard solution (standard), test solution (sample), spike solution and phosphate buffer solution pH 6.8 as the mobile phase. Saccharin sodium levels in hard candy were calculated and determined using a calibration curve with a straight line equation. Then the detected solution was calculated to the treatment level, theoretical, recovery, average treatment level, Relative Percent Difference (RPD) (%) or relative difference, and 2/3 CV Horwitz using spike solution. The test results of saccharin sodium levels in hard candy are eligible for an acceptable %Recovery of 90-107% with SP 1 results of 103.86% and SP 2 of 100.51%. The test results were not detected in the chromatogram of solution (01 L; 07; 08), but were detected in the standard solution and spike solution, namely at λ 221 nm with Rt of 22.255 minutes (standard solution) and 22.258 minutes (spike solution). In addition, the data obtained is accurate (meets the precision requirements of %RPD < 2/3 CV Horwitz) with the results of 3.3313% < 4.3357. And the standard curve has met the linearity requirements (r ≥ 0.999) with the result of r = 0.99994